Pengembangan E-LKPD Fikih Berbasis CTL pada Materi Wudhu Menggunakan Platform Wizer.Me di Madrasah Tsanawiyah - Herawati, Susi; Ramadhani, Aulia Mesya; Demina, Demina; Eliwatis, Eliwatis; Khairat, Annisaul (IAIN Pontianak, 2024)
This research is motivated by the learning of fiqh, which is one of the subjects taught at madrasah tsanawiyah, this is part of Islamic religious learning which aims to direct and lead students to the right path and in accordance with the teachings of the Islamic religion. This research aims to develop a CTL-based Fiqh E-LKPD on ablution material using the wizer.me platform at Madrasah Tsanawiyah. The research method used is research and development (RD). Meanwhile, the development model used is the ADDIE development model. The average percentage result of Contextual Teaching and Learning (CTL) based fiqh ELKPD validation is 85.83% with a very valid category. Meanwhile, the percentage of class VII A assessments completed by 6 students on CTL based E-LKPD obtained a score of 89.33% in the very practical category, coupled with the results of the teacher response questionnaire which obtained 85% in the very practical category. In other words, the CTL based Fiqh ELKPD developed can be used in class VII Fiqh learning at MTs Thawalib Gunung Padang Panjang.